Ability of an altered functional coupling between resting-state networks to predict behavioral outcomes in subcortical ischemic stroke: A longitudinal study - Li, Yongxin; Yu, Zeyun; Wu, Ping; Chen, Jiaxu (Frontiers in Aging Neuroscience, 2022)
Stroke can be viewed as an acute disruption of an individual’s connectome caused by a focal or widespread loss of blood flow. Although individuals exhibit connectivity changes in multiple functional networks after stroke, the neural mechanisms that underlie the longitudinal reorganization of the connectivity patterns are still unclear. The aim of this study was to determine whether brain network connectivity patterns after stroke can predict longitudinal behavioral outcomes. Nineteen stroke patients with subcortical lesions underwent two sessions of resting-state functional magnetic resonance imaging scanning with a one-month interval. By independent component analysis, the functional connectivity within and between multiple brain networks (including the default mode network, dorsal attention network, limbic network, visual network and frontoparietal network) was disrupted after stroke and partial recovery at the second time point. Additionally, regression analyses revealed that the connectivity between the limbic and dorsal attention network at the first time point showed sufficient reliability in predicting the clinical scores (Fugl-Meyer Assessment and Neurological Deficit Scores) at the second time point. The overall findings suggest that functional coupling between the dorsal attention and limbic network after stroke can be regarded as a biomarker to predict longitudinal clinical outcomes in motor function and the degree of neurological functional deficit. Overall, the present study provided a novel opportunity to improve prognostic ability after subcortical strokes.